2020
DOI: 10.3390/genes11070741
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ACE2 Genetic Variability among Populations Highlights a Possible Link with COVID-19-Related Neurological Complications

Abstract: Angiotensin-converting enzyme 2 (ACE2) has been recognized as the entry receptor of the novel severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2). Structural and sequence variants in ACE2 gene may affect its expression in different tissues and determine a differential response to SARS-Cov-2 infection and the COVID-19-related phenotype. The present study investigated the genetic variability of ACE2 in terms of single nucleotide variants (SNVs), copy number variations (CNVs), and expression quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 29 publications
0
64
0
Order By: Relevance
“…However, this variant deserves further investigation in a larger COVID-19 cohorts as well as functional studies. Concerning the other two variants, the recurrent c.439+4A>G (rs2285666) intronic variant has been previously reported by Strafella et al [14] and by Asselta et al [15] in two different Italian cohorts representative of the country's population. The variant is located in the intron 3 in a splice site region of the gene.…”
Section: Resultsmentioning
confidence: 70%
“…However, this variant deserves further investigation in a larger COVID-19 cohorts as well as functional studies. Concerning the other two variants, the recurrent c.439+4A>G (rs2285666) intronic variant has been previously reported by Strafella et al [14] and by Asselta et al [15] in two different Italian cohorts representative of the country's population. The variant is located in the intron 3 in a splice site region of the gene.…”
Section: Resultsmentioning
confidence: 70%
“…Among all the common exonic variants, some very recent studies done on ACE2 variants reported population-based frequency differences for a single nucleotide variant (SNV) rs2285666 (also called G8790A) (Asselta et al, 2020;Cao et al, 2020;Strafella et al, 2020). This variant of ACE2 was significantly different for Europeans (0.2), than the East Asians (0.55) (Asselta et al, 2020;Cao et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Several differences in clinical manifestations and complications of COVID-19 patients have been observed suggesting variability in the disease process [ 19 ]. Genetic variants in the host human genome, can in part explain the broad inter-individual variation of disease susceptibility and/or severity [ 6 , 19 , 20 , 21 ]. Moreover, the expression levels of human genes encoding the main proteins involved in this mechanism could be critical for the susceptibility, symptoms and outcome of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%